Post-transcriptional control of human ether-a-go-go-related gene potassium channel protein by alpha-adrenergic receptor stimulation - Chen, Jian; Chen, Kun; Sroubek, Jakub; Wu, Zhi-Yuan; Thomas, Dierk; Bian, Jin-Song; McDonald, Thomas V. (Molecular pharmacology, 2010)
Stimulation of alpha1-adrenoreceptors (alpha1-AR) acutely alters ion channel behavior via several signaling pathways [calcium and protein kinase C (PKC)]. Little is known about sustained alpha1-adrenergic/PKC signaling and channel regulation as may occur during cardiovascular disease states. Here we describe the effects of prolonged alpha1A-AR and PKC activity on human ether-a-go-go-related gene (HERG) K(+) channels (Kv11.1) expressed in a heterologous expression system. Stimulation of alpha1A-AR with phenylephrine or direct activation of PKC with phorbol ester increased HERG channel protein abundance and K(+) current density in a time- and dose-dependent manner. Channel augmentation reached a steady-state plateau within 24 h with a 2- to 6-fold induction. Phorbol ester and moderate alpha1A-AR stimulation enhanced HERG abundance in a PKC-dependent fashion but with stronger alpha1A-adrenergic stimulation; protein kinase A (PKA)-dependent activity also contributed. Comparable channel induction of other cardiac K(+) channels was not seen in this system. Comparison of wild-type HERG and channels with either mutated PKC phosphorylation sites (HERGDeltaPKC) or mutated PKA phosphorylation sites (HERGDeltaPKA) suggested that the mechanisms of augmentation of HERG by the two kinases were partially overlapping. The PKC-dependent effect was largely due to enhanced synthetic rates. Stimulation of alpha1-AR in cultured rat neonatal cardiac myocytes also enhanced the abundance of ERG channels. These findings show that alpha1A-AR stimulation is capable of influencing the balance of HERG channel synthesis and degradation via multiple signaling pathways, a process that may have relevance in cardiac diseases and treatment.
Gesehen am 03.03.2023